HiRes Ultra Series Recall: Failure Rates and Revision Speech Recognition Outcomes. Issue 7 (August 2022) - Lindquist, Nathan R.; Cass, Nathan D.; Patro, Ankita; Perkins, Elizabeth L.; Gifford, René H.; Haynes, David S.; Holder, Jourdan T.
Abstract : Objective: To report Advanced Bionics (AB) Ultra (V1) and Ultra 3D (V1) cochlear implant (CI) electrode failures and revision speech recognition outcomes for patients at a large CI program. Study Design: Retrospective case series. Setting: Tertiary referral center. Patients: Patients receiving Ultra (V1) or Ultra 3D (V1) devices as of September 21, 2021. Main Outcome Measures: Failure rate, revision surgery, speech recognition scores. Results: To data, 65 (21.1%) of the 308 implanted devices are known failures, with 63 (20.5%) associated with the recent voluntary field corrective action (FCA). Average time to failure was 2.2 ± 1.1 years. Fifty-two patients (82.5%) elected for revision surgery. Among adults, immediate prerevision scores demonstrated a significant decrease from best-achieved scores with the faulty implant, with mean difference of −15.2% ( p = 0.0115) for consonant-nucleus-consonant (CNC) and −27.3% ( p < 0.0001) for AzBio in quiet. By 3 months postactivation of the revised device, CNC ( p = 0.9766) and AzBio in quiet ( p = 0.9501) scores were not significantly different than best prerevision scores. Overall, 15 of 19 patients regained or improved their best prerevision CNC score. The current trajectory for FCA device failures is approximately 6% per year. Conclusion: Compared to manufacturer reporting, a high number of patients experienced hard failures of the Ultra (V1) and Ultra 3D (V1) devices. Early identification of failures is possibly because of the diligent use of electrical field imaging testing. Most patients affected by the FCA regain or exceed their prefailure speech recognition score as soon as 3 months after revision surgery.